An intronic mutation in Chd7 creates a cryptic splice site, causing aberrant splicing in a mouse model of CHARGE syndrome - Jacqueline M. Ogier (Nature Portfolio, 2018)
Abstract Alternate splicing is a critical regulator of gene expression in eukaryotes, however genetic mutations can cause erroneous splicing and disease. Most recorded splicing disorders are caused by mutations of splice donor/acceptor sites, however intronic mutations can affect splicing. Clinical exome analyses largely ignore intronic sequence, limiting the detection of mutations to within coding regions. We describe ‘Trooper’, a novel mouse model of CHARGE syndrome harbouring a pathogenic point mutation in Chd7. The mutation is 18 nucleotides upstream of exon 10 and creates a cryptic acceptor site, causing exon skipping and partial intron retention. This mutation, though detectable in exome sequence, was initially dismissed by computational filtering due to its intronic location. The Trooper strain exhibited many of the previously described CHARGE-like anomalies of CHD7 deficient mouse lines; including hearing impairment, vestibular hypoplasia and growth retardation. However, more common features such as facial asymmetry and circling were rarely observed. Recognition of these characteristic features prompted manual reexamination of Chd7 sequence and subsequent validation of the intronic mutation, highlighting the importance of phenotyping alongside exome analyses. The Trooper mouse serves as a valuable model of atypical CHARGE syndrome and reveals a molecular mechanism that may underpin milder clinical presentation of the syndrome.